EFFECTIVE ORGANIZATION OF THE EDUCATIONAL PROCESS IN HIGHER EDUCATION BASED ON THE PEDAGOGY OF COOPERATION (Scientific journal of the Fergana State University, 2023)
This article discusses the methods of effective organization of the educational process in higher educational institutions based on the pedagogy of cooperation, as well as important aspects of the principles of teamwork in improving the effectiveness of the lesson.